2023
DOI: 10.1371/journal.pone.0295586
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characterization of ischemic heart disease at different altitudes: A nationwide population-based analysis from 2011 to 2021 in Ecuador

Esteban Ortiz-Prado,
Juan S. Izquierdo-Condoy,
Raúl Fernández-Naranjo
et al.

Abstract: Background Cardiovascular diseases, including ischemic heart disease, are the leading cause of premature death and disability worldwide. While traditional risk factors such as smoking, obesity, and diabetes have been thoroughly investigated, non-traditional risk factors like high-altitude exposure remain underexplored. This study aims to examine the incidence and mortality rates of ischemic heart disease over the past decade in Ecuador, a country with a diverse altitude profile spanning from 0 to 4,300 meters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…There is no consensus in the results of these studies. Thus, when hospital admissions and mortality in the high-altitude locations of Ecuador were compared to low altitude, high altitude yielded protective effect [ 20 ], but when patients with heart failure were considered, high altitude increased the risk of adverse events [ 36 ]. Furthermore, the largest published cohort of workers exposed to high altitude during the high-altitude railroad construction [ 30 ] could not clarify the risks for workers with CAD, because the diagnosis was a contraindication to work and subjects were not allowed to ascend to the worksite.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no consensus in the results of these studies. Thus, when hospital admissions and mortality in the high-altitude locations of Ecuador were compared to low altitude, high altitude yielded protective effect [ 20 ], but when patients with heart failure were considered, high altitude increased the risk of adverse events [ 36 ]. Furthermore, the largest published cohort of workers exposed to high altitude during the high-altitude railroad construction [ 30 ] could not clarify the risks for workers with CAD, because the diagnosis was a contraindication to work and subjects were not allowed to ascend to the worksite.…”
Section: Discussionmentioning
confidence: 99%
“…Even more research efforts have been put to characterize cardiovascular adaptation and the risk at high altitude. Earlier studies in Central Asia and more recent studies in Ecuador have shown low cardiovascular risk in the highlanders [ 4 – 6 , 20 ]. At present, epidemiological evidence on cardiovascular disease (CVD) at high altitude is conflicting [ 16 ], when lower ischemic heart disease burden in some studies [ 20 ] may be higher in the other [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation